Problem of psychological and psycholinguistic model validity - Victoria V. Dobrova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the paper the problem of validity of psychological and psycholinguistic models is discussed. The ontological and operational approaches to the validity of models are analyzed, representatives of which propose various criteria to the model validity. The requirements to the psychological and psycholinguistic models are given. The examples of psychological and psycholinguistic models are analyzed in order to verify their validity. Psychological modeling does not mean the exact correspondence of the model and its original. It combines the criteria of different approaches.